Study on Comparison Mechanical Properties of Concrete using Eggshell Powder and Palm Oil Bottom Ash as a Replacement Material in Concrete - Jamaluddin, Muhammad Firman; Ahmad Jeni, Mohamad Luthfi; Hilmi Kosnin (Progress in Engineering Application and Technology, 2024)
This study focuses on producing Eggshell Powder (ESP) as a substitute for cement and Palm Oil Bottom Ash (POBA) as a replacement for fine aggregate in concrete mixtures. The primary objective is to assess the density and compressive strength of concrete when alternative substances are used as replacements for cement. The second goal is to evaluate the effectiveness of Eggshell Powder (ESP) and Palm Oil Bottom Ash (POBA) as replacement materials for concrete. The third aim is to compare the performance of concrete incorporating Eggshell Powder (ESP) and Palm Oil Bottom Ash with that of normal concrete. The fourth objective is to analyze the environmental impact of utilizing alternative materials at every stage of their life cycle, from extraction to processing, use, and disposal. This research is motivated by the rising cost of materials in concrete and the desire to reduce dependence on natural resources for fine aggregate. Additionally, the study aims to mitigate the environmental impact caused by the burning of Palm Oil Bottom Ash. In the methodology, eggshells are collected from consumed eggs instead of being discarded with the peel, serving as a material for use in concrete. Palm Oil Bottom Ash is obtained from a palm oil mill near Bukit Pasir for testing. The design mix is calculated using the Design of Normal Concrete Mix (DOE Method), with replacement percentages of cement and fine aggregate set at 0%, 10%, 20%, and 30%. Density tests, water absorption tests, and compression tests are conducted on 48 concrete cubes at the ages of 7 and 28 days. The experimental results indicate that concrete samples with 30% ESP and POBA exhibit the highest compressive strength and the lowest water absorption ability compared to those with 20% and 30% ESP and POBA. The concrete sample containing 30% ESP and POBA closely approaches the results of normal concrete, specifically achieving a grade 30. This shows that the optimal content of ESP and POBA in the concrete mix is 30%.